Method for preparing layered hydrotalcite-like PVC heat stabilizer from vermiculite
By pretreating and modifying vermiculite, a layered hydrotalcite PVC thermal stabilizer with excellent thermal stability and anti-aging properties was prepared, which solved the problem of insufficient stability under high temperature conditions in the prior art, and realized the Improve product quality and quality.
Patent Information
- Application Number
- CN202411406872.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing layered hydrotalcite PVC thermal stabilizer for vermiculite preparation is insufficient in stable performance under high temperature conditions and needs further improvement to improve its quality and quality.
By pretreating vermiculite, a colloidal solution was prepared, and lanthanum nitrate and sodium hydroxide were added to it, sonicated and dispersed, and finally polyethylene glycol was added for modification, a layer with excellent thermal stability and anti-aging properties was prepared. Hydroxytalc PVC heat stabilizer.
It has achieved good thermal stability and excellent anti-aging properties of PVC thermal stabilizer for layered hydrotalcites in vermiculite, ensuring the quality and quality of the product, and is suitable for industrial production and marketing promotion.
Smart Images

Figure BDA0005076864020000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC production, in particular to a method for preparing a layered hydrotalcite-like PVC heat stabilizer by using vermiculite. Background Art
[0002] Vermiculite is a natural, inorganic, non-toxic mineral that expands under high temperature. It is a relatively rare mineral and belongs to silicate. Its crystal structure is monoclinic, and its appearance looks very similar to mica. Vermiculite is produced when certain granites are hydrated. It is usually produced at the same time as asbestos.
[0003] Polyvinyl chloride plastic has excellent mechanical and electrical properties and low overall cost. It has been widely used in industrial and agricultural production and daily life for many years.
[0004] Hydrotalcite is a layered double metal hydroxide, which is widely used in many fields such as heat stabilizer, catalyst, catalyst carrier, flame retardant, pesticide, sewage treatment agent, electrorheological modifier, medicine, pharmaceutical carrier, etc., and has high economic value.
[0005] In the patent document with application number "CN202210827967.1" and titled "A method for preparing layered hydrotalcite-like PVC heat stabilizer from vermiculite", it is recorded that "vermiculite is pretreated to prepare nanoscale vermiculite flakes, fluoride, ammonia water and water are added, and a series of reactions such as ultrasonic dispersion are carried out to obtain layered powder layered hydrotalcite and silica products, thereby realizing the preparation of vermiculite functional products, which are applied to PVC products to improve the thermal stability of PVC; the present invention can directly prepare vermiculite-based layered powder products, has the coupling of reaction and separation, and has the function of peeling layered vermiculite, and the reaction temperature of this method is low, which has the advantage of low energy consumption; in addition, the treatment agent fluoride can be recycled and reused, which is suitable for industrial production and other advantages. The present invention realizes the separation of the silicon oxygen octahedron and aluminum oxygen tetrahedron structures of vermiculite, and the prepared product has the advantages of excellent high temperature resistance and anti-aging performance, and at the same time has flame retardant properties, and also has certain infrared and ultraviolet blocking capabilities."
[0006] Although the layered hydrotalcite-like PVC heat stabilizer produced in the above patent document has the advantages of anti-aging, its stability under high temperature conditions is relatively insufficient and still needs further improvement. Based on this, the present invention provides a method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite to solve the above technical problems. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite. The prepared layered hydrotalcite-like PVC heat stabilizer from vermiculite not only has good thermal stability but also has excellent anti-aging performance, thereby effectively ensuring its quality.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite, comprising the following steps:
[0010] S1, pre-treating vermiculite;
[0011] S2, preparing a colloidal solution using the pretreated vermiculite;
[0012] S3, adding lanthanum nitrate to the obtained colloidal solution to prepare a hydrotalcite base material;
[0013] S4. Modifying the obtained hydrotalcite base material to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0014] The present invention is further configured as follows: in step S1, the process of pre-treating the vermiculite is as follows:
[0015] The vermiculite is washed with deionized water for 2 to 4 times, and dried at a temperature of 50 to 60° C. for 50 to 52 hours to obtain washed vermiculite;
[0016] The washed vermiculite is placed in the prepared solution at a solid-liquid ratio of 0.05-0.25 g / mL, stirred at 26-30° C. and 120-220 r / min for 8-10 hours, filtered, and dried at 50-60° C. to constant weight to obtain a first material;
[0017] The first material is placed in a muffle furnace and calcined in an air atmosphere at 800-850° C. for 2-3 minutes;
[0018] Then calcining for 3 to 4 minutes at 900 to 910° C. in an air atmosphere, and cooling to room temperature to obtain a second material;
[0019] The obtained second material is washed with deionized water for 6 to 8 times, and dried at a temperature of 50 to 60° C. to a constant weight to obtain pretreated vermiculite.
[0020] The present invention is further configured as follows: the prepared solution is prepared by mixing sodium chlorite and distilled water at a solid-liquid ratio of 0.02 to 0.0.4 g / mL.
[0021] The present invention is further configured as follows: in step S2, the process of preparing the colloidal solution using the pretreated vermiculite is as follows:
[0022] The pretreated vermiculite is placed in deionized water at a solid-liquid ratio of 0.05-0.08 g / mL, and is cut and crushed at a high speed of 15000-18000 r / min for 60-100 min;
[0023] Then centrifuge at 8200-8600 r / min for 10-12 min, take the supernatant and obtain a colloidal solution.
[0024] The present invention is further configured as follows: in step S3, the process of preparing the hydrotalcite base material is as follows:
[0025] Add lanthanum nitrate to the obtained colloidal solution and ultrasonically treat for 10 to 14 minutes, then add a sodium hydroxide solution with a concentration of 0.6 to 0.8%, and then centrifuge, wash the obtained separated product with deionized water for 2 to 4 times, and dry it at a temperature of 50 to 60° C. to constant weight to obtain a first base material;
[0026] The first base material is placed in deionized water and ultrasonically dispersed for 20 to 30 minutes at a solid-liquid ratio of 0.02 to 0.12 g / mL, and then treated at 120 to 130° C. for 25 to 30 hours. After cooling, centrifugation is performed, and the separated solid is dried at 50 to 60° C. to constant weight to obtain a second base material, namely, a hydrotalcite base material;
[0027] Wherein, the addition amount of the lanthanum nitrate is 0.12-0.32% of the mass of the colloidal solution;
[0028] The addition amount of the sodium hydroxide solution is 22-25% of the mass of the colloid solution.
[0029] The present invention is further configured as follows: in step S4, the process of modifying the obtained hydrotalcite base material is as follows:
[0030] The hydrotalcite base material is ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.05 to 0.12 g / mL for 20 to 30 minutes, polyethylene glycol is added thereto, and ultrasonic treatment is performed at 60° C. for 200 to 230 minutes;
[0031] Then the mixture is filtered, washed with anhydrous ethanol and deionized water for 2 to 4 times, dried at 50 to 60° C. to a constant weight, and ground to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0032] The present invention is further configured as follows: the addition amount of the polyethylene glycol is 5.2-6.2% of the mass of the hydrotalcite base material.
[0033] The present invention is further configured as follows: in the step S4, the obtained layered hydrotalcite-like PVC heat stabilizer is further subjected to the steps of inspection and metering and packaging in sequence.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] In the present invention, vermiculite and the like are used as raw materials, the vermiculite is pretreated, a colloidal solution is prepared by using the pretreated vermiculite, lanthanum nitrate is added to the obtained colloidal solution, a hydrotalcite base material is prepared, and finally the obtained hydrotalcite base material is modified to obtain a layered hydrotalcite-like PVC heat stabilizer. The layered hydrotalcite-like PVC heat stabilizer prepared by the vermiculite prepared by the present invention not only has good thermal stability, but also has excellent anti-aging performance, and its quality and quality are effectively guaranteed. The method for preparing a layered hydrotalcite-like PVC heat stabilizer by using vermiculite provided by the present invention has a broader market prospect and is more suitable for promotion. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite, comprising the following steps:
[0039] S1. Pre-treat the vermiculite.
[0040] Among them, the process of pretreatment of vermiculite is as follows:
[0041] The vermiculite was washed twice with deionized water and dried at 50° C. for 50 h to obtain washed vermiculite;
[0042] The washed vermiculite was placed in the prepared solution at a solid-liquid ratio of 0.05 g / mL, stirred at 26° C. and 120 r / min for 8 h, filtered, and dried at 50° C. to constant weight to obtain a first material;
[0043] The first material is placed in a muffle furnace and calcined at 800° C. for 2 min in an air atmosphere;
[0044] Then calcining at 900° C. for 3 min in an air atmosphere, and cooling to room temperature to obtain a second material;
[0045] The obtained second material was washed with deionized water for 6 times, and dried at 50° C. to a constant weight to obtain pretreated vermiculite.
[0046] Furthermore, the prepared solution is prepared by mixing sodium chlorite and distilled water at a solid-liquid ratio of 0.02 g / mL.
[0047] In this embodiment, it should be noted that the vermiculite was purchased from Xinjiang Yuli Xinlong Vermiculite Co., Ltd.
[0048] S2. preparing a colloidal solution using the pretreated vermiculite.
[0049] The process of preparing the colloidal solution using the pretreated vermiculite is as follows:
[0050] The pretreated vermiculite was placed in deionized water at a solid-liquid ratio of 0.05 g / mL and crushed at a high speed of 15000 r / min for 60 min;
[0051] Then centrifuge at 8200 r / min for 10 min, take the supernatant and obtain a colloidal solution.
[0052] S3. Add lanthanum nitrate to the obtained colloidal solution to prepare a hydrotalcite base material.
[0053] Wherein, the process of preparing the hydrotalcite base material is as follows:
[0054] Add lanthanum nitrate to the obtained colloidal solution and ultrasonically treat for 10 minutes, then add a 0.6% sodium hydroxide solution, and then centrifuge to separate, wash the separated product twice with deionized water, and dry at 50° C. to constant weight to obtain a first base material;
[0055] The first base material was ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.02 g / mL for 20 minutes, then treated at 120° C. for 25 hours, cooled, and centrifuged. The separated solid was dried at 50° C. to constant weight to obtain a second base material, namely, a hydrotalcite base material;
[0056] Wherein, the addition amount of lanthanum nitrate is 0.12% of the mass of the colloidal solution;
[0057] The addition amount of the sodium hydroxide solution is 22% of the mass of the colloid solution.
[0058] S4. Modifying the obtained hydrotalcite base material to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0059] The process of modifying the obtained hydrotalcite base material is as follows:
[0060] The hydrotalcite base material was ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.05 g / mL for 20 min, polyethylene glycol was added thereto, and ultrasonic treatment was performed at 60° C. for 200 min;
[0061] Then the mixture was filtered, washed twice with anhydrous ethanol and deionized water respectively, dried at 50° C. to constant weight, and ground to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0062] Furthermore, the added amount of polyethylene glycol is 5.2% of the mass of the hydrotalcite base material.
[0063] In addition, the method also includes the steps of sequentially inspecting and metering and packaging the obtained layered hydrotalcite-like PVC heat stabilizer.
[0064] In this embodiment, it should be noted that polyethylene glycol was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0065] Example 2
[0066] This embodiment provides a method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite, comprising the following steps:
[0067] S1. Pre-treat the vermiculite.
[0068] Among them, the process of pretreatment of vermiculite is as follows:
[0069] The vermiculite was washed with deionized water for three times, and dried at 55°C for 51 hours to obtain washed vermiculite;
[0070] The washed vermiculite was placed in the prepared solution at a solid-liquid ratio of 0.15 g / mL, stirred at 28° C. and 170 r / min for 9 hours, filtered, and dried at 55° C. to constant weight to obtain a first material;
[0071] The first material was placed in a muffle furnace and calcined at 825° C. for 3 min in an air atmosphere;
[0072] The mixture was then calcined at 905°C for 4 min in an air atmosphere and cooled to room temperature to obtain a second material;
[0073] The obtained second material was washed with deionized water for 7 times, and dried at 55° C. to a constant weight to obtain pretreated vermiculite.
[0074] Furthermore, the prepared solution is prepared by mixing sodium chlorite and distilled water at a solid-liquid ratio of 0.03 g / mL.
[0075] In this embodiment, it should be noted that the vermiculite was purchased from Xinjiang Yuli Xinlong Vermiculite Co., Ltd.
[0076] S2. preparing a colloidal solution using the pretreated vermiculite.
[0077] The process of preparing the colloidal solution using the pretreated vermiculite is as follows:
[0078] The pretreated vermiculite was placed in deionized water at a solid-liquid ratio of 0.06 g / mL and crushed at a high speed of 16500 r / min for 80 min.
[0079] Then centrifuge at 8400 r / min for 11 min, take the supernatant and obtain a colloidal solution.
[0080] S3. Add lanthanum nitrate to the obtained colloidal solution to prepare a hydrotalcite base material.
[0081] Wherein, the process of preparing the hydrotalcite base material is as follows:
[0082] Add lanthanum nitrate to the obtained colloidal solution and ultrasonically treat for 12 minutes, then add a 0.7% sodium hydroxide solution, and then centrifuge, wash the obtained separated product with deionized water for 3 times, and dry it at a temperature of 50-60° C. to constant weight to obtain a first base material;
[0083] The first base material was ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.07 g / mL for 25 minutes, then treated at 125° C. for 27 hours, cooled, and centrifuged. The separated solid was dried at 55° C. to constant weight to obtain a second base material, namely, a hydrotalcite base material;
[0084] Wherein, the addition amount of lanthanum nitrate is 0.22% of the mass of the colloidal solution;
[0085] The addition amount of the sodium hydroxide solution is 23% of the mass of the colloid solution.
[0086] S4. Modifying the obtained hydrotalcite base material to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0087] The process of modifying the obtained hydrotalcite base material is as follows:
[0088] The hydrotalcite base material was ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.08 g / mL for 25 min, polyethylene glycol was added thereto, and ultrasonic treatment was performed at 60°C for 215 min;
[0089] Then the mixture was filtered, washed three times with anhydrous ethanol and deionized water respectively, dried at 55° C. to constant weight, and ground to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0090] Furthermore, the added amount of polyethylene glycol is 5.7% of the mass of the hydrotalcite base material.
[0091] In addition, the method also includes the steps of sequentially inspecting and metering and packaging the obtained layered hydrotalcite-like PVC heat stabilizer.
[0092] In this embodiment, it should be noted that polyethylene glycol was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0093] Example 3
[0094] This embodiment provides a method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite, comprising the following steps:
[0095] S1. Pre-treat the vermiculite.
[0096] Among them, the process of pretreatment of vermiculite is as follows:
[0097] The vermiculite was washed with deionized water for 4 times, and dried at 60° C. for 52 h to obtain washed vermiculite;
[0098] The washed vermiculite was placed in the prepared solution at a solid-liquid ratio of 0.25 g / mL, stirred at 30° C. and 220 r / min for 10 h, filtered, and dried at 60° C. to constant weight to obtain a first material;
[0099] The first material is placed in a muffle furnace and calcined at 850° C. for 3 min in an air atmosphere;
[0100] Then calcining for 3 to 4 minutes at 900 to 910° C. in an air atmosphere, and cooling to room temperature to obtain a second material;
[0101] The obtained second material was washed 8 times with deionized water, and dried at 60° C. to constant weight to obtain pretreated vermiculite.
[0102] Furthermore, the prepared solution is prepared by mixing sodium chlorite and distilled water at a solid-liquid ratio of 0.0.4 g / mL.
[0103] In this embodiment, it should be noted that the vermiculite was purchased from Xinjiang Yuli Xinlong Vermiculite Co., Ltd.
[0104] S2. preparing a colloidal solution using the pretreated vermiculite.
[0105] The process of preparing the colloidal solution using the pretreated vermiculite is as follows:
[0106] The pretreated vermiculite was placed in deionized water at a solid-liquid ratio of 0.08 g / mL and crushed at a high speed of 18000 r / min for 100 min.
[0107] Then centrifuge at 8600 r / min for 12 min, take the supernatant and obtain a colloidal solution.
[0108] S3. Add lanthanum nitrate to the obtained colloidal solution to prepare a hydrotalcite base material.
[0109] Wherein, the process of preparing the hydrotalcite base material is as follows:
[0110] Add lanthanum nitrate to the obtained colloidal solution and ultrasonically treat for 14 minutes, then add a 0.8% sodium hydroxide solution, and then centrifuge, wash the obtained separated product with deionized water for 4 times, and dry it at 60° C. to constant weight to obtain a first base material;
[0111] The first base material was ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.12 g / mL for 30 minutes, then treated at 130° C. for 30 hours, cooled, and centrifuged. The separated solid was dried at 60° C. to constant weight to obtain a second base material, namely, a hydrotalcite base material;
[0112] Wherein, the addition amount of lanthanum nitrate is 0.32% of the mass of the colloidal solution;
[0113] The addition amount of the sodium hydroxide solution is 25% of the mass of the colloid solution.
[0114] S4. Modifying the obtained hydrotalcite base material to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0115] The process of modifying the obtained hydrotalcite base material is as follows:
[0116] The hydrotalcite base material was ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.12 g / mL for 30 min, polyethylene glycol was added thereto, and ultrasonic treatment was performed at 60°C for 230 min;
[0117] Then the mixture was filtered, washed with anhydrous ethanol and deionized water for four times respectively, dried at 60° C. to constant weight, and ground to obtain a layered hydrotalcite-like PVC heat stabilizer.
[0118] Furthermore, the added amount of polyethylene glycol is 6.2% of the mass of the hydrotalcite base material.
[0119] In addition, the method also includes the steps of sequentially inspecting and metering and packaging the obtained layered hydrotalcite-like PVC heat stabilizer.
[0120] In this embodiment, it should be noted that polyethylene glycol was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0121] Comparative Example 1: The difference from Example 1 is that the vermiculite is not pretreated in this example.
[0122] Comparative Example 2: The difference from Example 1 is that the hydrotalcite base material is not modified in this example.
[0123] Performance test: The layered hydrotalcite-like PVC heat stabilizer samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the layered hydrotalcite-like PVC heat stabilizers provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:
[0124] 1. Thermal stability test: The test method is to add 50 parts by mass of DOP (di-2-ethylhexyl phthalate) and 5 parts by mass of layered hydrotalcite-like PVC thermal stabilizer to 100 parts by mass of PVC resin, mix on a high-speed mixer for 5 minutes, then mix on a double-roll mill for 6 minutes at 150°C, roll into a sheet sample with a thickness of 1mm on a tablet press, and then cut the sheet sample into a 2cm×2cm test piece. The sample is placed in a heat aging test box at 200±1°C for static aging experiment.
[0125] 2. Anti-aging test: The test method is to test the whiteness of the PVC test piece every 10 minutes according to the thermal stability test method and GB / T2913-1982 standard.
[0126] The obtained test data are recorded in Table 1 and Table 2 below:
[0127] Table 1 Thermal stability test results of each group of layered hydrotalcite-like PVC thermal stabilizers
[0128] Group 200℃ thermal stability time (min) Example 1 Group 138 Example 2 Group 140 Example 3 Group 138 Comparison group 1 130 Comparison of 2 groups 125
[0129] Table 2 Anti-aging performance test results of each group of layered hydrotalcite-like PVC heat stabilizers
[0130]
[0131]
[0132] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the layered hydrotalcite-like PVC heat stabilizer prepared by the vermiculite prepared by the present invention not only has good thermal stability, but also has excellent anti-aging performance, effectively ensuring its quality. This shows that the method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite provided by the present invention has a broader market prospect and is more suitable for promotion.
[0133] In the present invention, vermiculite and the like are used as raw materials, the vermiculite is pretreated, a colloidal solution is prepared by using the pretreated vermiculite, lanthanum nitrate is added to the obtained colloidal solution to prepare a hydrotalcite base material, and finally the obtained hydrotalcite base material is modified to obtain a layered hydrotalcite-like PVC heat stabilizer. The layered hydrotalcite-like PVC heat stabilizer prepared by the vermiculite prepared by the present invention not only has good thermal stability, but also has excellent anti-aging performance, and effectively guarantees its quality.
[0134] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0135] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite, characterized in that: The following steps are involved: S1, pre-treating vermiculite; S2, preparing a colloidal solution using the pretreated vermiculite; S3, adding lanthanum nitrate to the obtained colloidal solution to prepare a hydrotalcite base material; S4. Modifying the obtained hydrotalcite base material to obtain a layered hydrotalcite-like PVC heat stabilizer.
2. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 1, characterized in that: In step S1, the process of pre-treating vermiculite is as follows: The vermiculite is washed with deionized water for 2 to 4 times, and dried at a temperature of 50 to 60° C. for 50 to 52 hours to obtain washed vermiculite; The washed vermiculite is placed in the prepared solution at a solid-liquid ratio of 0.05-0.25 g / mL, stirred at 26-30° C. and 120-220 r / min for 8-10 hours, filtered, and dried at 50-60° C. to constant weight to obtain a first material; The first material is placed in a muffle furnace and calcined in an air atmosphere at 800-850° C. for 2-3 minutes; Then calcining for 3 to 4 minutes at 900 to 910° C. in an air atmosphere, and cooling to room temperature to obtain a second material; The obtained second material is washed with deionized water for 6 to 8 times, and dried at a temperature of 50 to 60° C. to a constant weight to obtain pretreated vermiculite.
3. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 2, characterized in that: The prepared solution is prepared by mixing sodium chlorite and distilled water at a solid-liquid ratio of 0.02 to 0.0.4 g / mL.
4. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 1, characterized in that: In step S2, the process of preparing the colloidal solution using the pretreated vermiculite is as follows: The pretreated vermiculite is placed in deionized water at a solid-liquid ratio of 0.05-0.08 g / mL, and is cut and crushed at a high speed of 15000-18000 r / min for 60-100 min; Then centrifuge at 8200-8600 r / min for 10-12 min, take the supernatant and obtain a colloidal solution.
5. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 1, characterized in that: In step S3, the process of preparing the hydrotalcite base material is as follows: Add lanthanum nitrate to the obtained colloidal solution and ultrasonically treat for 10 to 14 minutes, then add a sodium hydroxide solution with a concentration of 0.6 to 0.8%, and then centrifuge, wash the obtained separated product with deionized water for 2 to 4 times, and dry it at a temperature of 50 to 60° C. to constant weight to obtain a first base material; The first base material is placed in deionized water and ultrasonically dispersed for 20 to 30 minutes at a solid-liquid ratio of 0.02 to 0.12 g / mL, and then treated at 120 to 130° C. for 25 to 30 hours. After cooling, centrifugation is performed, and the separated solid is dried at 50 to 60° C. to constant weight to obtain a second base material, namely, a hydrotalcite base material; Wherein, the addition amount of the lanthanum nitrate is 0.12-0.32% of the mass of the colloidal solution; The amount of sodium hydroxide solution added is 22-25% of the mass of the colloidal solution.
6. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 1, characterized in that: In step S4, the process of modifying the obtained hydrotalcite base material is as follows: The hydrotalcite base material is ultrasonically dispersed in deionized water at a solid-liquid ratio of 0.05 to 0.12 g / mL for 20 to 30 minutes, polyethylene glycol is added thereto, and ultrasonic treatment is performed at 60° C. for 200 to 230 minutes; Then the mixture is filtered, washed with anhydrous ethanol and deionized water for 2 to 4 times, dried at 50 to 60° C. to a constant weight, and ground to obtain a layered hydrotalcite-like PVC heat stabilizer.
7. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 6, characterized in that: The added amount of the polyethylene glycol is 5.2-6.2% of the mass of the hydrotalcite base material.
8. The method for preparing a layered hydrotalcite-like PVC heat stabilizer from vermiculite according to claim 1, characterized in that: In the step S4, the obtained layered hydrotalcite-like PVC heat stabilizer is also subjected to inspection and metering and packaging steps in sequence.
Citation Information
Patent Citations
Method for preparing layered hydrotalcite-like PVC heat stabilizer from vermiculite
CN115028939A
Preparation method of magnesium aluminum lanthanum type hydrotalcite PVC composite heat stabilizer
CN103508480A